Tales of the Atelier - Zaadstra, Pieter; Pieter Zaadstra Art Studio (Tas.) (Gravelly Beach, Tasmania : Pieter Zaadstra Art Studio)
"Tales of the Atelier are items of opinion by artist and author Pieter Zaadstra. These memoirs are quirky articles presented here and in future magazines."--Inside back cover.
"Memoirs on: ekphrasis, impressionism, expressionism, atelier life, art insights, studio hints"--Volume 1 title page.
"Published biannually (December and June)"--40° South Pty Ltd website.
Description based on: [December 2015] ; title from cover
Keywords: Art, Australian -- Tasmania -- 21st century -- Pictorial works -- Periodicals; Drawing -- Tasmania -- 21st century -- Pictorial works -- Periodicals; Art -- History -- Periodicals; Artists' studios -- Tasmania -- Periodicals; Australian